ANALISIS KECELAKAAN LALU LINTAS (STUDI KASUS - JALAN RAYA UNGARAN - BAWEN) - Wicaksono, Dendy; Fathurochman, Rizky Akbar; Riyanto, Bambang; Wicaksono, YI. (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Traffic accident is the problem that need serious attention because the risk that can be caused. Therefore it need study to do analysis for the traffic accident data.This final project take place in Ungaran-Bawen road in Semarang city. That road are artery road with very crowded traffic.That road are connecting Semarang as one of big city in Central Java with the city around , example : Solo, Magelang, and Yogyakarta. The purpose of this study are to identify location and the cause of traffic accident in order to give the solution to reduce the accident that will happen. Data analysis which we do to know relation usher variable having an effect on to accident amount use aid of computer program of SPSS, while for determination of location of accident gristle (blackspot), using statistical technique control traffic. Traffic accident caused by some factor, that is human (driver), environmental, vehicle and roads. From result analyse data, human (driver) represent primary factor of cause the happening of accident (66,89%). Careless driver is most driver behavior often cause the happening of accident (72,45%). Type of accident and most collision often be happened is front - front collision (50,85%), with motorcycle (53,78%) as most type vehicle often be involved by a accident. The most common time of the accident was at 12.00 – 18.00 (31,74%) and the most common driver job of the accident is employee (61,86%).